2000
DOI: 10.1097/00004770-200009000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Hydroxide and Tumor Growth Factor-β on Collagen Synthesis in Subcultures I and V of Osteoblasts

Abstract: Collagen protein synthesis by osteoblasts is influenced by transforming growth factor-beta (TGF-beta 1) and is essential to bone formation. The effectiveness of TGF-beta 1 depends on efficient delivery of the growth factor to target cells, adequate binding to cell surface receptors, and an optimum environment for promotion of collagen synthesis. The effects of calcium hydroxide (Ca(OH)2), TGF-beta 1, and Ca(OH)2/TGF-beta 1 co-administration on total protein, collagen protein, and noncollagen protein synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Comparable results were seen by treating an osteoblastic cell line or porcine bone cells with IGF‐I 32, 33. The addition of TGF‐β1 to late osteoblast cell cultures increased the collagen production 34. The combination of growth factors like IGF‐I and TGF‐β1 had a synergistic effect on matrix apposition of fetal rat calvaria in vitro 35…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were seen by treating an osteoblastic cell line or porcine bone cells with IGF‐I 32, 33. The addition of TGF‐β1 to late osteoblast cell cultures increased the collagen production 34. The combination of growth factors like IGF‐I and TGF‐β1 had a synergistic effect on matrix apposition of fetal rat calvaria in vitro 35…”
Section: Discussionmentioning
confidence: 99%
“…The cells showed a similar proliferation compared to the controls but a significantly enhanced production of procollagen 1 independently from the incubation time with the implant. Other studies were also able to demonstrate that the application of IGF-I or TGF-b1 into the culture medium enhanced the production of collagen in osteoblast culture [31][32][33][34][35]. These studies used freshly prepared growth factor solutions or the growth factor was incorporated into a membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, this could be explained by the inhibitory effects of TGF-β1 in all of the groups. As previously shown, the combination of Ca(OH) 2 and TGF-β1 is anabolic in cultures of osteoblasts ( Jaunberzins et al 2000).…”
Section: Discussionmentioning
confidence: 60%
“…Pfeilschifter et al (1988) found that TGF-β1 inhibits bone resorption. As previously shown, the combination of Ca(OH) 2 and TGF-β1 is anabolic in cultures of osteoblasts ( Jaunberzins et al 2000). This inhibition may be due to down-regulation of IL-6 production.…”
Section: Discussionmentioning
confidence: 68%